INTEGRATION OF VOCATIONAL HIGH SCHOOL CURRICULUM WITH INDUSTRY NEEDS BASED ON OUTCOME-BASED EDUCATION - Maharani Fadhiyah Haifani; Rochmah Wijayanti; Anam Sutopo; Sutama (Universitas Islam Negeri Mataram, 2025)
This study aims to describe the process of integrating the vocational high school (Sekolah MenengahKejuruan/SMK) curriculum with the needs of the industrial sector through the implementation of the Outcome-Based Education (OBE) approach. The study is motivated by the gap between the competencies of SMK graduatesand the demands of the labor market, necessitating curriculum reform oriented toward achieving learningoutcomes. A descriptive qualitative approach with a case study Design was employed and conducted at SMKMuhammadiyah 1 Baturetno, Wonogiri Regency. Data were collected through interviews, observations, anddocument analysis, and were analyzed using an interactive analysis model with triangulation techniques to ensuredata validity. The findings indicate that the school has implemented the principles of link and match throughcollaboration with industry in curriculum planning, internship program implementation, and the strengthening ofteacher competencies. However, gaps remain between students’ learning outcomes and industry competencystandards, particularly in non-technical skills such as communication, teamwork, and work discipline. Theimplementation of OBE provides strategic direction for vocational education to become more oriented towardlearning outcomes relevant to industry needs. Therefore, continuous synergy between schools and industry is a keyfactor in producing competent, adaptive, and competitive graduates in the era of Industry 4.0.